Voltammetric Method for Determination of Glutathione on a Gold-Carbon-Containing Electrode; Inorganic Materials; Vol. 56, iss. 11 - Gashevskaya A. S. Anna Sergeevna; Dorozhko E. V. Elena Vladimirovna; Korotkova E. I. Elena Ivanovna; Pashkovskaya E. A. Elvira Aleksandrovna; Voronova O. A. Olesya Aleksandrovna; Plotnikov E. V. Evgeny Vladimirovich; Derina K. V. Kseniya Vladimirovna; Lipskikh O. I. Olga Ivanovna (2020, 2020)
Title screen